1994
DOI: 10.1007/bf02184158
|View full text |Cite
|
Sign up to set email alerts
|

Pigment interactions in chlorosomes of various green bacteria

Abstract: Resonance Raman experiments were performed on different green bacteria. With blue excitation, i.e. under Soret resonance or preresonance conditions, resonance Raman contributions were essentially arising from the chlorosome pigments. By comparing these spectra and those of isolated chlorosomes, it is possible to evaluate how the latter retain their native structure during the isolation procedures. The structure of bacteriochlorophyll oligomers in chlorosomes was interspecifically compared, in bacteriochlorophy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
19
0

Year Published

1996
1996
2015
2015

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 24 publications
3
19
0
Order By: Relevance
“…This is notably the case for the methine bridge stretching modes; this band, observed at about 1600 cm Ϫ1 when the central magnesium is six-coordinated, is up-shifted to 1610 -1615 cm Ϫ1 for five-coordinated magnesium. In resonance Raman spectra of chl b molecules, this band is extremely weak at best (23,24), and thus, determining the coordination state of the central magnesium proves much more difficult. There is an intense band in resonance Raman spectra of chl b arising from C a -C b stretching modes (23) that is sensitive to the molecular core size.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is notably the case for the methine bridge stretching modes; this band, observed at about 1600 cm Ϫ1 when the central magnesium is six-coordinated, is up-shifted to 1610 -1615 cm Ϫ1 for five-coordinated magnesium. In resonance Raman spectra of chl b molecules, this band is extremely weak at best (23,24), and thus, determining the coordination state of the central magnesium proves much more difficult. There is an intense band in resonance Raman spectra of chl b arising from C a -C b stretching modes (23) that is sensitive to the molecular core size.…”
Section: Resultsmentioning
confidence: 99%
“…In spectra obtained with 457.9 nm excitation, it may be noted that the bands arising from the stretching modes of the keto carbonyl groups of chl b exhibit only low intensity. As discussed above, this excitation line induces a resonance mainly with the B x component of the Soret electronic transition, thus favoring the contribution of stretching modes of the formyl carbonyl of these molecules, and not of the keto carbonyl group (24). The increase in intensity of these bands for 441.6 nm excitation may reflect an increase in chl a resonance and/or the location of this wavelength within the B y absorption band of chl b.…”
mentioning
confidence: 88%
“…The shifts of 13-C@O stretching mode in the chlorosomes were almost the same, ca. 60 cm À1 , indicating that the strength of the hydrogen bond between the two groups of BChls was quite similar in C-and Dchlorosomes [27]. RR spectroscopy showed that the basic structural motif of BChl self-aggregates in natural chlorosomes is essentially the same between them.…”
Section: Rr Spectramentioning
confidence: 97%
“…Around 1,660 cm -1 , the attribution of the contributing bands to acetyl (or formyl) or to keto stretching modes is not straightforward. Formyl group contributions may however be assessed using the fact that they lie on the X axis of the B(Chl) molecules, and thus are preferentially enhanced when excited in the Bx transition (Feiler et al 1994a). Other factors, such as the dielectric properties of the environment may also influence these frequencies, though to a lesser extent ).…”
Section: Resonance Raman Spectra Of Photosynthetic Pigmentsmentioning
confidence: 98%